Dlk1 regulates quiescence in calcitonin receptor-mutant muscle stem cells. (8th December 2020) - Zhang, Lidan; Kubota, Manami; Nakamura, Ayasa; Kaji, Takayuki; Seno, Shigeto; Uezumi, Akiyoshi; Andersen, Ditte Caroline; Jensen, Charlotte Harken; Fukada, So-ichiro
Abstract: Muscle stem cells, also called muscle satellite cells (MuSCs), are responsible for skeletal muscle regeneration and are sustained in an undifferentiated and quiescent state under steady conditions. The calcitonin receptor (CalcR)-protein kinase A (PKA)-Yes-associated protein 1 (Yap1) axis is one pathway that maintains quiescence in MuSCs. Although CalcR signaling in MuSCs has been identified, the critical CalcR signaling targets are incompletely understood. Here, we show the relevance between the ectopic expression of delta-like non-canonical Notch ligand 1 (Dlk1) and the impaired quiescent state in CalcR-conditional knockout (cKO) MuSCs. Dlk1 expression was rarely detected in both quiescent and proliferating MuSCs in control mice, whereas Dlk1 expression was remarkably increased in CalcR-cKO MuSCs at both the mRNA and protein levels. It is noteworthy that all Ki67 + non-quiescent CalcR-cKO MuSCs express Dlk1, and non-quiescent CalcR-cKO MuSCs are enriched in the Dlk1 + fraction by cell sorting. Using mutant mice, we demonstrated that PKA-activation or Yap1-depletion suppressed Dlk1 expression in CalcR-cKO MuSCs, which suggests that the CalcR-PKA-Yap1 axis inhibits the expression of Dlk1 in quiescent MuSCs. Moreover, the loss of Dlk1 rescued the quiescent state in CalcR-cKO MuSCs, which indicates that the ectopic expression of Dlk1 disturbs quiescence in CalcR-cKO. Collectively, our results suggest that ectopically expressed Dlk1 is responsible for the impaired quiescence in CalcR-cKO MuSCs. Abstract : Calcitonin receptor (CalcR)-mutant muscle stem cells ectopically express delta-like non-canonical Notch ligand 1 (Dlk1). The Dlk1 expression marks all non-quiescent muscle stem cells in CalcR-mutant muscle stem cells. The loss of Dlk1 rescues the impaired quiescent state in CalcR-mutant muscle stem cells.